Decision-Making in Evidence-Based Practice in Rehabilitation Medicine: Proposing a Fourth Factor. (May 2020) - Gutenbrunner, Christoph; Nugraha, Boya
Abstract : Abstract: According to the Sackett's model, evidence-based decision-making in medicine includes the clinical judgment, scientific evidence, and the patient's values and preferences. In rehabilitation medicine, it is well established that according to the International Classification of Functioning, Disability and Health model, contextual factors (environmental and personal factors) influence a person's individual level of functioning. This article argues that component of the health system (eg, health insurance coverage, availability of services, treatments, and assistive devices) and the service organization (eg, spectrum and training level of health professionals, availability of diagnostic, and treatment devices) have relevant influence on the decision-making in the individual case. For that reason, it is proposed to add the health system and service organization as a fourth factor to the model of evidence-based decision-making. Taking the influence of it into consideration and to describe it clearly will improve transparency of the decision-making process and the acceptance of health care users. This fourth factor is also relevant for other medical fields. However, the proposed factor and its components need to be discussed and further elucidated scientifically.